2009
DOI: 10.1080/01431160802698919
|View full text |Cite
|
Sign up to set email alerts
|

Global irrigated area map (GIAM), derived from remote sensing, for the end of the last millennium

Abstract: A Global Irrigated Area Map (GIAM) has been produced for the end of the last millennium using multiple satellite sensor, secondary, Google Earth and groundtruth data. The data included: (a) Advanced Very High Resolution Radiometer (AVHRR) 3-band and Normalized Difference Vegetation Index (NDVI) 10 km monthly time-series for 1997-1999, (b) Syste`me pour l'Observation de la Terre Vegetation (SPOT VGT) NDVI 1 km monthly time series for 1999, (c) East Anglia University Climate Research Unit (CRU) rainfall 50km mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
313
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(336 citation statements)
references
References 25 publications
3
313
1
2
Order By: Relevance
“…Category I occupies 0.8% of all land surface. A detailed world irrigation map was produced by Thenkabail et al (2009), whose results are similar in relation to the arid regions identified in this study. Category I does not always accurately present cultivated areas.…”
Section: Category I (Irrigated Areas and Oases)mentioning
confidence: 99%
“…Category I occupies 0.8% of all land surface. A detailed world irrigation map was produced by Thenkabail et al (2009), whose results are similar in relation to the arid regions identified in this study. Category I does not always accurately present cultivated areas.…”
Section: Category I (Irrigated Areas and Oases)mentioning
confidence: 99%
“…Remote sensing is widely used to classify and map croplands over regional areas (Thenkabail et al 2009;Thenkabail, Gamage, and Smakhin 2004). The methods exploit both the absolute greenness as well as the greenness dynamics, or land surface phenology, of the disparate crop types (Chang et al 2007;Shao et al 2010;Turker and Arikan 2005;Wardlow, Egbert, and Kastens 2007;Zhong, Gong, and Biging 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To secure the environmental flow towards the lower stream under different hydrological conditions, a water allocation plan has been implemented since 2000. For example, in a normal year (i.e., the annual flow from Yingluoxia reaches 1580 million m 3 ), the flow through Zhengyixia should be no less than 950 million m 3 . Since 2000, diversion of the In the midstream area, the most common crops are corn and winter wheat.…”
Section: Study Areamentioning
confidence: 99%
“…Currently, the irrigated cropland produces more than 40% of the total cereal yield worldwide [1,2]. Globally, about 54% of the total irrigated area is dependent on surface water (SW) such as rivers, lakes, artificial canals and reservoirs [3]. Meanwhile, in arid and semi-arid regions of the world where surface water is not abundantly available, groundwater (GW) abstraction is often required for irrigation purposes.…”
Section: Introductionmentioning
confidence: 99%